Synthesis of core-crosslinked star polymers via organocatalyzed living radical polymerization - Zheng, Yichao (2021)
Core-crosslinked star polymers were prepared using organocatalyzed living radical polymerization via a “grafting-through” approach. A PBA homopolymer, an amphiphilic PMMA–PPEGA block copolymer, and a hard-soft PMMA–PBA block copolymer were synthesized as macroinitiators, where PBA is poly(butyl acrylate), PMMA is poly(methyl methacrylate), and PPEGA is poly(poly(ethylene glycol) methyl ether acrylate). The macroinitiators were utilized in the polymerizations of crosslinkable divinyl monomers, generating core-crosslinked star polymers in 40–80% yields. The PMMA–PBA block copolymer macroinitiator was synthesized from a PMMA with an unsaturated chain end (PMMA–Y) via an addition-fragmentation chain transfer method. The ease of the handling of PMMA–Y is an advantage of the use of PMMA–Y. One-pot synthesis of a PBA star was also successful, giving a star in a relatively high yield (73%). The one-pot synthesis offers a practical approach for synthesizing a core-crosslinked star. The present approach is free from metals and odorous compounds, which is an attractive feature of the present approach.